Semantic Interpretation in Experimental Typography Creation - Ade Lose Hermanto, Yon (KnE Social Sciences, 2023)
This research aims to reveal how to design by utilizing semantics to reinforce the meaning of a message through typography. The methods used in this research are: exposing, redefining, managing, prototyping, and trendspotting. The experiment was carried out by changing the nouns, verbs, and adjectives from the letters of the alphabet into visual semantics without changing the meaning of the words used. Semantic design for typography can be used by changing one or more letters into a visual form that still conveys the meaning and nature of the words used. The result of this study is the design of semantic interpretation in typography that strengthens and clarifies meaning. Design can be applied in turning letters into illustrative forms, whether it only uses one letter in a word or can also use more than one letter to strengthen the meaning of a word. Keywords: semantics, interpretation, typography